1996
DOI: 10.1164/ajrccm.154.4.8887593
|View full text |Cite
|
Sign up to set email alerts
|

Western red cedar dust exposure and lung function: a dose-response relationship.

Abstract: The relationship between levels of cumulative red cedar dust exposure and decline in lung function was explored in an 11-yr follow-up study of 243 sawmill workers who participated in at least two occasions. We also studied 140 office workers in a similar manner as control subjects. Workers with asthma were excluded from the analysis. During the period of the study, 916 personal and 216 area samples of dust were collected from the sawmill. Cumulative wood dust exposure was calculated for each sawmill worker acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…In other studies [3,10], relationships between wood dust exposure and decline in lung function have been revealed, especially among sawmill workers. Sawmill workers exposed to western red cedar were studied in an 11-yr follow-up study including 243 subjects [3]. Workers were divided into groups with mean average exposure between ,0.2 and .0.4 mg?m -3 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In other studies [3,10], relationships between wood dust exposure and decline in lung function have been revealed, especially among sawmill workers. Sawmill workers exposed to western red cedar were studied in an 11-yr follow-up study including 243 subjects [3]. Workers were divided into groups with mean average exposure between ,0.2 and .0.4 mg?m -3 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies describing the relationship between chronic obstructive pulmonary disease (COPD) and exposure to wood dust have shown conflicting results: while a number of studies have shown an association between decreased lung function and wood dust exposure [2][3][4], others found no such association [5][6][7][8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of all cases of occupational asthma due to wood dust has been reported to be some 6-11% (8). Asthma induced by western red cedar has been frequently documented for sawmill workers, with an apparent dose-response relationship (10)(11)(12)(13)(14). The studies proposing a relationship between exposure to other softwood species and asthma have used self-reported asthma (11) and clinically diagnosed asthma (15,16) as outcomes.…”
mentioning
confidence: 99%